Multipliers of Distributions Spaces (Global Journal of Science Frontier Research, 2013)
In this paper we consider multipliers of distributions spaces. We obtain some characterizations of various multipliers spaces similar to those of multipliers of Banach algebras.
Keywords: distribution; multiplier; convolution